Mechanical ventilation guidelines in lung lobectomy surgery and the quest to improve outcomes - Ansari, Bilal; Parotto, Matteo (Journal of Thoracic Disease; Vol 10, No 12 (December 30, 2018): Journal of Thoracic Disease, 2018)
Mechanical ventilation is a life-saving treatment that changed patient care opportunities in perioperative and critical care medicine. Unfortunately, soon after its introduction into clinical practice it became evident how positive pressure ventilation held the potential to contribute to, and cause, lung injury—a phenomenon referred to as ventilator induced lung injury (VILI) (1).